PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP RETURN ON ASSETS (ROA) PADA POLITEKNIK LP3I JAKARTA KAMPUS JAKARTA UTARA TAHUN 2014-2018 - Featy Octaviany; Nanik Mutmainnah (JURNAL LENTERA AKUNTANSI, 2019)
This study aims to determine cash turnover, account receivable turnover and its effect on Return On Assets (ROA) at the LP3I polytechnic, Nort Jakarta Campus. To carry out economic activitiesa company must have the ability to process financial statement data as a tool to provide information that can be used ini economic decision making. The components of working capital namely cash turnover, accounts receivable turnover and Return On Assets (ROA) are needed by a company to determine whether or not an company is efficient in carrying out its business or activities. In this study the author conducted a case study at the LP3I Jakarta Polytechnic, North Jakarta Campus. With the problems studied are the components of working capital consisting of two sub-variables, namely cash turnover (X1) and receivable turnover (X2) as independent variables and Retun On Assets (ROA) (Y) as the dependent variable. To analyze the comparison of cash turnover performance, accounts receivable turnover and Return On Assets (ROA), the author uses a comparison analysis of these ratios which is made a comparison chart and descriptive statistics test. In addition to making comparisons, the author uses classical assumptions, multiple linear regression, correlation coefficient, coefficient of determination, t test and f test. From the results of the analysis, it shows the performance of cash turnover, accounts receivable turnover and Return On Assets (ROA). Then from the results of statistical analysis on testing the coefficient of determination against the very strong influence between cash turnover and receivable turnover on Return On Assets (ROA) which is equal to 97.21%, while the F test results indicate that cash turnover and receivable turnover have a significant towards Return On Assets (ROA). The conclusion of the research is, all variable X cash turnover and accounts receivable turnover are significant to Return On Assets (ROA).Keywords: Cash Turnover, Receivable Turnover and Return On Assets (ROA)